AN ANALYSIS OF STUDENTS ANXIETY IN SPEAKING ENGLISH OF THE SECOND GRADE STUDENTS OF MA DDI LAKATAN - Marzuki Marzuki (Universitas Madako Tolitoli, 2022)
This research aimed to find out what are the causes of students anxiety in speaking mainly in English subject. This type of research was a qualitative research method in which the research location is MA DDI Lakatan, whose data sources consist of 5 students namely Rf, Sm, Hk, Sw, Sp. The data collection method included interviews, questionnaires, and documentation. The data analysis technique was qualitative descriptive analysis (data reduction, data display and conclusion drawer). The result of interview showed that the students felt anxiety which were caused by some aspects; they fear of making mistake, less confident when they asked to speak in front of the class, fear of being ridiculed by peers, and had limited by vocabulary. The result of questionnaire also stated that the second grade students of MA DDI Lakatan felt anxiety in speaking English.